ANALISIS KONSEP JUAL BELI DAN TEORI GHARAR DALAM PERSPEKTIF EKONOMI SYARIAH STUDI KASUS PENIMBUNAN MINYAKITA - Irfan Fadilah, Muhamad; Jauharunnisa, Sevana; Ardillah Tidzkar, Misbah; Laila Salsabila, Zahra; Marlina, Lina (Ekonomi Syariah STAI Sangatta Kutai Timur, 2025)
This study aims to examine the concept of buying and selling as well as the theory of gharar from the perspective of Islamic economics, using the case of Minyakita hoarding in Indonesia. In Islamic principles, trade is founded on justice, transparency, and mutual consent between parties; however, the hoarding of essential goods creates artificial scarcity and abnormal price increases, leading to uncertainty (gharar) in transactions. Within the framework of fiqh muamalah, gharar is strictly prohibited because it involves elements of speculation and market manipulation that can potentially harm society. Using a qualitative approach through a review of Islamic economic literature and an analysis of regulatory frameworks governing the distribution of basic commodities, the findings reveal that Minyakita hoarding constitutes gharar fahish (major gharar), which adversely affects economic stability, public access to essential goods, and overall social welfare. Such practices not only contravene the fundamental principles of trade but also violate the objectives of maqasid al-shariah, particularly the preservation of property (hifz al-mal) and the promotion of public welfare; therefore, stringent government supervision and stronger awareness of Islamic business ethics are crucial to ensure that trade practices remain fair, transparent, and conducive to sustainable economic development.